2013
DOI: 10.1371/journal.pone.0080405
|View full text |Cite
|
Sign up to set email alerts
|

The Basal Nodosaurid Ankylosaur Europelta carbonensis n. gen., n. sp. from the Lower Cretaceous (Lower Albian) Escucha Formation of Northeastern Spain

Abstract: Nodosaurids are poorly known from the Lower Cretaceous of Europe. Two associated ankylosaur skeletons excavated from the lower Albian carbonaceous member of the Escucha Formation near Ariño in northeastern Teruel, Spain reveal nearly all the diagnostic recognized character that define nodosaurid ankylosaurs. These new specimens comprise a new genus and species of nodosaurid ankylosaur and represent the single most complete taxon of ankylosaur from the Cretaceous of Europe. These two specimens were examined and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 92 publications
(176 reference statements)
5
57
0
Order By: Relevance
“…There are some isolated ankylosaur remains known from Aptian and Albian sediments of the UK, but amongst these only the taxon Anoplosaurus is considered to be valid (Carpenter 2001, Vickaryous et al, 2004; the remainder are from indeterminate ankylosaurs. Kirkland et al (2013) Clay Formation contradicts previous the hypothesis that these two taxa occupied nonoverlapping biostratigraphical ranges (Norman, 1987), as noted by Barrett and Maidment (2011). There appears to have been sympatric populations of both taxa for at least a period of time during the Valanginian.…”
Section: Polacanthus and Hylaeosaurus Biostratigraphymentioning
confidence: 55%
See 1 more Smart Citation
“…There are some isolated ankylosaur remains known from Aptian and Albian sediments of the UK, but amongst these only the taxon Anoplosaurus is considered to be valid (Carpenter 2001, Vickaryous et al, 2004; the remainder are from indeterminate ankylosaurs. Kirkland et al (2013) Clay Formation contradicts previous the hypothesis that these two taxa occupied nonoverlapping biostratigraphical ranges (Norman, 1987), as noted by Barrett and Maidment (2011). There appears to have been sympatric populations of both taxa for at least a period of time during the Valanginian.…”
Section: Polacanthus and Hylaeosaurus Biostratigraphymentioning
confidence: 55%
“…The nature of Hylaeosaurus sacral armour remains unknown. Arbour et al (2011) plotted the three categories of sacral shield morphology stratigraphically and found that dinosaurs with Category 2 shields were restricted to the late Jurassic and early to mid Cretaceous of Europe and the USA, and this supports Kirkland et al (2013) that the Polacanthidae were replaced by nodosaurs bearing mostly Category 3 sacral shields by the mid Cretaceous in Europe. Arbour et al (2011) also point out that one of the reasons for the failure of some ankylosaur analyses (e.g.…”
Section: Armour In Polacanthusmentioning
confidence: 86%
“…During the late Early Cretaceous two main groups of quadruped dinosaurs (sauropods and ankylosaurs) inhabited Europe, including the Iberian Peninsula, though the osteological record is scarce (Martin et al, 1993;Upchurch et al, 2004;Vickaryous et al, 2004;Buffetaut and Nori, 2012;Kirkland et al, 2013). Sauropod tracks are globally distributed over the entire world during the Mesozoic, with some significant tracksites in the "mid" Cretaceous in Korea and North America (Thulborn, 1990;Lockley et al, 1994;Wright, 2005;Mannion and Upchurch, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Both faunas are similar in sharing leptoceratopsians, derived non-hadrosaurid hadrosauroids, nodosaurids, and dromaeosaurids (e.g., Dalla Vecchia, 2009;Kirkland et al, 2013). Notably, the European hadrosauroid taxon Tethyshadros insularis was recovered by Prieto-Márquez et al (2016a) as the sister taxon of Hadrosauridae and therefore as one closer node to that clade than the Appalachian taxon Claosaurus agilis and as two closer nodes than Lophorhothon atopus.…”
Section: Comparisons Of Appalachian and European Coniacian-campanian mentioning
confidence: 96%
“…Secondly, ornithomimosaurs are fairly common and widespread on Appalachia during the Late Cretaceous (e.g., Weishampel et al, 2004;Erickson and Ebersole, 2011;Schwimmer et al, 2015), whereas during the same time only one probable occurrence is known from Europe (Mateus et al, 2009). European nodosaurids seem to form a distinct clade, the Struthiosaurinae (Kirkland et al, 2013), while the majority of Appalachian taxa (Texasetes pleurohalio, the unnamed Paw Paw juvenile, Silvisaurus condrayi, Niobrarasaurus coleii) have consistently not been found as close relatives of any 'struthiosaurines' (e.g., Carpenter, 2001;Vickaryous et al, 2004;Arbour et al, 2016). These major differences affirm that Appalachian faunas were distinct from European ones, and suggest along with the data recounted herein on Laramidian and Appalachian non-avian dinosaurs that Appalachia itself was a distinct non-avian dinosaur faunal zone during the majority of the Late Cretaceous.…”
Section: Comparisons Of Appalachian and European Coniacian-campanian mentioning
confidence: 99%